Parents and sport activity of their preschool children - Kropej, Veronika L. (Kinesiologia Slovenica, 2002)
The aim of this research is to determine the possibilities of achieving higher sports activity among preschool children. We have used a questionnaire for children's parents to gather data for this research. The sample included 154 parents. This research has shown that there are factors that could increase sport activities among preschool children and that these factors are directly influenced by the children's parents. These factors are: parents' involvement in sport activities, spending active holidays together, sociability, and their parents' positive attitude towards sport.
Keywords: okolje; otroci; predšolski otroci; raziskave; starši; šport; športna aktivnost; vpliv